Crowd reactions to entrepreneurial failure in rewards-based crowdfunding: A psychological contract theory perspective - Swati Oberoi; Smita Srivastava; Vishal K. Gupta; Rohit Joshi; Atul Mehta (Journal of Risk and Financial Management, 2022)
Rewards-based crowdfunding (RBC) has recently gained popularity as an alternative means of finance to help entrepreneurs bring novel projects to life. We theorize that crowdfunding backers perceive an implicit psychological contract with campaign creators. When promised rewards fail to materialize post fundraising, backers may perceive entrepreneurs' failure to deliver rewards as a violation of their psychological contract with him or her. Drawing on psychological contract theory and using Eisenhardt's comparative case methodology, we generate insights about crowd reactions to creators' failure to deliver rewards to backers. Our research generates the novel insight that in the event of delivery failure, backers who perceive a transactional psychological contract with creators are more likely to display negative emotional reactions, while backers who perceive a relational psychological contract are more likely to display positive emotional reactions. Furthermore, we identify three progressive stages of backers' interaction with creators in failed RBC campaigns, 'committing', 'crisis handling', and 'coping-up' and highlight the crowds' emotional valence associated with each stage. Our analyses of the campaign comments reveal insights of interest to RBC players and hold implications for the future development of crowdfunding.
Keywords: 650; crowdfunding; emotional valence; entrepreneurial failure; failure to deliver rewards; Kickstarter.com; psychological contract theory; rewards-based crowdfunding